Metodología COPSOQ: evaluación y prevención de los riesgos psicosociales en los servidores públicos del Hospital Dr. Aníbal González Álava de Calceta 2023 - Basurto Pita, Yandry Patricio (2025)
The present research project aimed to propose preventive measures to mitigate psychosocial risks among the staff of the Dr. Aníbal González Álava Hospital in Calceta, applying the COPSOQ methodology as a diagnostic and analytical tool. The study was developed using a mixed approach, employing bibliographic, descriptive, and field methods. Interviews and surveys were conducted with the hospital’s 102 public servants, using the COPSOQ questionnaire to evaluate dimensions related to job demands, social support, autonomy, insecurity, and psychosocial well-being. The data were processed through digital tabulation and analyzed using Likert-type scales, allowing for the identification of patterns, trends, and staff perceptions. The results revealed that the main risk factors correspond to work overload, extended shifts, care-related pressure, lack of recognition, communication and leadership deficiencies, as well as imbalances between effort and reward. These conditions are associated with high levels of stress, emotional exhaustion, anxiety, and burnout symptoms, which affect motivation, physical and mental health, and the quality of care provided. The application of the COPSOQ made it possible to identify the most critical psychosocial risks, providing key inputs for the development of an action plan aimed at redesigning workloads, strengthening social support through participatory leadership, implementing emotional well-being programs, and establishing policies that promote work–life balance. In this way, the project seeks to consolidate an efficient, harmonious hospital committed to the well-being of its team and the community.